ICT and the tension between old and new: the human factor - Gorniak-Kocikowska, Krystyna (Journal of Information, Communication and Ethics in Society, 2008)
Purpose The purpose of this paper is to deepen the understanding of tensions between old and new in the emerging global society driven by information and communication technology (ICT); and to argue that creation of a theory of this society would contribute in the easing of these tensions. Design/methodology/approach The methods used in this paper are mostly analytical, descriptive, and qualitative. An analysis of the creation and development of ICT from a mathematical discipline of computer science to a universal tool and a driving force of the emerging global society, a development which is paralleled by the commercialization of ICT, is followed by two case studies illustrating the tensions between old and new and the role ICT plays in them. One case is centered on the challenges of traditional models of education by new, ICT-friendly approaches, like the Multiple Intelligences Theory; the other addresses tensions between old and new that in many societies presently take the form of tensions between local/national and global. Findings A claim is formed that the existing tensions between old and new are closely linked to the tensions between the two most common forms of society, inclusive (egalitarian) and exclusive (elitist). Originality/value The paper will help understand some of the reactions to the process of globalization. It can serve as a tool for assessment and prediction regarding this process. Lastly, the paper contains a justification of merit in the creation of a “grass root” theory of an ICT-driven global society built on a universally accepted ethical foundation. © 2008, Emerald Group Publishing Limited
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00314 tex.type: [object Object]
Keywords: Communication technologies; Education; Ethics; Globalization; Information society; Language; dept.phi; peer-reviewed

From computer ethics to the ethics of global ICT society - Gorniak-Kocikowska, Krystyna (Library Hi Tech, 2007)
Purpose - The purpose of this paper is to address the place of computer/ICT ethics in the global ICT society driven by knowledge economy. Design/methodology/approach - The paper focuses on three main issues: the evolution of the name of the leading technology of our times and, accordingly, the evolution of the name of the society in which this technology plays the leading role; some ethical dilemmas that the global ICT society will need to solve; global ICT ethics and the knowledge economy. Findings - The paper suggests that global ICT ethics should be an ethics focusing on the dynamics of the relationship between the weak and the strong, the rich and the poor, the healthy and the sick worldwide - and it should explore the ethical problems from the point of view of both parties involved. That way, Global ICT Ethics can have a truly communicative character, and it can become an ethics that will be both a co-creator and also a result of a democratic processes. Originality/value - This paper should interest anyone concerned with ICT and globalization.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-860-005-442-947 tex.unique-id: [object Object]
Keywords: Communication technologies; Ethics; Globalization; dept.phi; peer-reviewed

Book Review: The catholic church and antisemitism: poland, 1933–1939. by ronald modras. langhorne, penn.: harwood academic publisher, 1994. 429 pp. 48.00 - Gorniak-Kocikowska, Krystyna (Journal of Church and State, 1997)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-524-633-010-63X tex.type: [object Object]
Keywords: book.review; dept.phi

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, Krystyna (Science and Engineering Ethics, 1996)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer revolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe.
32 citations (Crossref) [2023-10-31] Citation Key Alias: pop00034 tex.type: [object Object]
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi

The roman catholic church in poland after the fall of communism - Gorniak-Kocikowska, Krystyna (Occasional Papers on Religion in Eastern Europe, 2020)
WOS:000574619500001
Keywords: dept.phi; peer-reviewed; ⛔ No DOI found

Human Intelligence and Artificial Intelligence in Collaboration: Change Management, Creative Performance, and Societal Expectations - Goralski, Margaret; Górniak-Kocikowska, Krystyna (Future of business and finance, 2026)
Keywords: Applications of artificial intelligence; Artificial intelligence; Artificial psychology; Change management; Collaboration; Creative performance; Creativity; Human intelligence; Societal expectations; dept.phi

The Factor of Listening in Karl Jaspers’ Philosophy of Communication - Górniak-Kocikowska, Krystyna (Philosophical Faith and the Future of Humanity, 2012)
Jaspers’ views on communication and his approach to the question of listening, both underwent an evolution in which World War II and the first years thereafter played a crucial role. In this process, Jaspers journeyed from listening to the great minds of the past, through an inward dialogue with them, to one-sided lecturing while his audience was engaged in a straight-line listening, to an intimate dialogue with those he considered like-minded, to a multi-faceted dialogue, and finally to listening to his contemporaries and learning how to practice transactional listening-in-conversation in the process of a multi-layered communication he called a loving struggle. This evolution, paralleled by the transition of Japers’ philosophy from local-centered to world-centered makes his thinking attractive and useful today.
Citation Key Alias: lens.org/035-525-517-724-768
Keywords: German Student; Great Mind; Nazi Regime; Political Involvement; Verbal Communication; dept.phi